Racism Issues on Papuans on Online News Media SuaraPapua.com and Idenera.com: A Critical Discourse Analysis - Yulianti, Deni Friska; Rosita, Nur; Wahyuni, Delvi (Universitas Negeri Padang, 2023)
This study utilizes Theo van Leeuwen's Critical Discourse Analysis to examine racism representation in Indonesian online news media SuaraPapua.com and Idenera.com. Employing a qualitative descriptive approach, data were drawn directly from articles on both platforms. Analysis reveals 14 instances of exclusion manifested through passivation, 8 nominalTizations, and 1 clause replacement. Despite variations, both platforms condemn racism against Papuans, often framing and marginalizing perpetrators without featuring them. SuaraPapua.com predominantly uses marginalization in reporting, whereas Idenera.com specifically identifies perpetrators such as military personnel (TNI), Satpol PP, mass organizations, and Indonesian officials like All Murtopa, Kopasus Commander, and Retired General Luhut Pandjaitan. This differential approach suggests a nuanced stance on addressing racism. While SuaraPapua.com employs a more generalized portrayal, Idenera.com adopts a more targeted approach by naming individuals involved. This research underscores the media's role in shaping perceptions of racism, highlighting variations in reporting strategies between platforms.